An extreme mutational hotspot in nlpD depends on transcriptional induction of rpoS. - Andrew D Farr; Christina Vasileiou; Peter A Lind; Paul B Rainey (PLoS Genetics)
Mutation rate varies within and between genomes. Within genomes, tracts of nucleotides, including short sequence repeats and palindromes, can cause localised elevation of mutation rate. Additional mechanisms remain poorly understood. Here we report an instance of extreme mutational bias in Pseudomonas fluorescens SBW25 associated with a single base-pair change in nlpD. These mutants frequently evolve in static microcosms, and have a cell-chaining (CC) phenotype. Analysis of 153 replicate populations revealed 137 independent instances of a C565T loss-of-function mutation at codon 189 (CAG to TAG (Q189*)). Fitness measures of alternative nlpD mutants did not explain the deterministic evolution of C565T mutants. Recognising that transcription can be mutagenic, and that codon 189 overlaps with a predicted promoter (rpoSp) for the adjacent stationary phase sigma factor, rpoS, transcription across this promoter region was measured. This confirmed rpoSp is induced in stationary phase and that C565T mutation caused significant elevation of transcription. The latter provided opportunity to determine the C565T mutation rate using a reporter-gene fused to rpoSp. Fluctuation assays estimate the C565T mutation rate to be ~5,000-fold higher than expected. In Pseudomonas, transcription of rpoS requires the positive activator PsrA, which we show also holds for SBW25. Fluctuation assays performed in a ∆psrA background showed a ~60-fold reduction in mutation rate confirming that the elevated rate of mutation at C565T mutation rate is dependent on induction of transcription. This hotspot suggests a generalisable phenomenon where the induction of transcription causes elevated mutation rates within defining regions of promoters.